Employee acceptance of digital transformation strategies: A paradox perspective - Sascha P. Klein; Patrick Spieth; Matthias Söllner (Journal of Product Innovation Management, 2024)
Digital transformation (DT) strategies often aim at innovating an organization's business models (BMs) and developing digital innovations. However, most of the DT strategies fail or result only in incremental innovation. Research predominantly identified critical management capabilities for DT success, neglecting the role of employees, although employee support is vital for the successful implementation of DT strategies. We conceptualize employee acceptance of DT strategies and draw on paradox theory and organizational change literature to shed light on the antecedents of employee acceptance. Using survey-based data from an incumbent introducing a DT strategy, we find empirical support that employees with a paradox mindset are likely to accept the DT strategy regardless of the expected scope of change, while a high scope of expected changes weakens the effect of a positive attitude toward change on acceptance. The findings contribute to understanding the micro-level aspects of DT and extend research emphasizing top-down management approaches in DT with an employee perspective. This study extends previous findings in innovation management that predominantly provide evidence on the acceptance of specific digital technologies and offer insights into the antecedents of DT strategy acceptance. We offer managers insights into how employees perceive DT strategies, which can help to leverage the potential of digital innovation.
Keywords: 650; digital transformation strategy; employee acceptance; paradox mindset; paradox theory